2012
DOI: 10.3176/oil.2012.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Co-Firing of Oil Shale and Biomass Fuels

Abstract: The effect of co-firing of biomass fuels with oil shale on combustion was investigated. Thermogravimetric analysis and differential scanning calorimetry were the tools used to perform the investigation. Since the combustion of biomass is highly exothermic, biomass fuels can serve as an appropriate fuel feedstock. Biomass fuels producing much volatile matter and containing less cellulose are good candidates for co-firing with oil shale. The biomass samples used in the study were hazelnut shell, wheat bran, popl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…[24][25][26] According to these studies, it has been reported that the value of activation energy decreases with the proportion of biomass mixed with SC and OS. [24][25][26] According to these studies, it has been reported that the value of activation energy decreases with the proportion of biomass mixed with SC and OS.…”
Section: Kinetic Analysis Of the Oxidation Processmentioning
confidence: 98%
See 2 more Smart Citations
“…[24][25][26] According to these studies, it has been reported that the value of activation energy decreases with the proportion of biomass mixed with SC and OS. [24][25][26] According to these studies, it has been reported that the value of activation energy decreases with the proportion of biomass mixed with SC and OS.…”
Section: Kinetic Analysis Of the Oxidation Processmentioning
confidence: 98%
“…Several studies have considered co-firing of unconventional fuels, including OS and SC, with other fuels (biomass, sludge, waste, etc) [23][24][25][26][27] to better understand the interactions between these fuels and support designers and operators when they evaluate the feasibility of different fuel blends for varying combinations in their installations. Trikkel et al performed combustion tests with SC and its mixtures with small additions of OS (from Estonia) on the 50 kW circulating fluidized bed combustion (CFBC) test rig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-isothermal kinetic methods have been used to study the thermal decomposition kinetics of residual carbonaceous materials, such as rubber [35], sugarcane bagasse [36], composting residues [37] and other bioresidues, especially lignocellulosic materials [34,11].…”
Section: Vyazovkin Kinetic Modelmentioning
confidence: 99%
“…Moreover, according to E. Özgür et al [11] one of the advantages of co-firing two different fuel types is that the power plant in operation can burn a supplementary fuel, which, depending on the fuel type and combustion system, can result in little or no additional costs for the new fuel. Co-firing with biomass can be friendlier environmentally because of lower emissions of greenhouse gases from carbon-neutral fuel in the blend.…”
Section: Introductionmentioning
confidence: 99%